하악골 신장술에서 압축자극을 통한 골재생시 TGF-β1, Osteonectin 및 BMP-4의 발현 - 박성진(Seong-Jin Park); 김욱규(Uk-Kyu Kim); 정인교(In-Kyo Chung); 황대석(Dae-Seok Hwang); 김용덕(Yong-Deok Kim); 신상훈(Sang-Hun Shin); 김철훈(Cheol-Hoon Kim); 변준호(June-Ho Byun) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2007)
Distraction osteogenesis(DO) is a technique of lengthning bone including soft tissue by gradual separation of surgically divided bone surfaces. Distraction osteogenesis combination with a compression stimulation(DO-CO) was a new technique by authors to enhance new bone quality and to shorten the consolidation period. The purpose of this study was to compare DO with DO combined with compression force in efficiency by evaluating the expression of TGF-β1, osteonectin and BMP-4 on bone regenerate in rabbit mandible. Fourty two rabbits were used for this experiment. On the control group, the distraction was carried out at the rate of 1 ㎜ per day to obtain the amount of 8 ㎜ distraction for 8 days. On the experimental group, the distraction was carried out at the rate of 1㎜ per day for 10 days, 3 days-latency period, and then the compression was carried out as counter direction 1 ㎜ per day for 2 days. After 0 day, 5 days, 13 days, 20 days, 27 days, 34 days and 41 days, three rabbits on each group were sacrificed and the distracted portion of mandible were cut and treated for RT-PCR observation. The level of expression of TGF-β1 and osteonectin were shown more and longer expression in the experimental group than in the control group. The expression of BMP-4 was maintained with high level during the entire experimental period in both groups. These findings suggested that DO with compression stimulation could be a favorable technique for obtaining a good new bone quality. KCI Citation Count: 0